OMAR IBN ’ABDUL ’AZIZ, KHALIFAH PEMERINTAHAN BANI UMAIYAH YANG BERTARAF MUJADDID - Berahim@Ibrahim, Ahmad Zaki (Journal of Al-Tamaddun, 2005)
Tajdid (reform) is an Islamic terminology and concept aims at returning mankind to the genuine teaching of Islam. Among the earliest mujaddid (reformer) in Islamic history is Omar b. ’Abdul ’Aziz, one of the Umayyad caliphs. Therefore, this article tries to analyze the role of Omar b. ’Abdul ’Aziz in the tajdid movement especially in the aspect of government, da?wa and knowledge.